Driving Sustainability: The Role of Managerial Ability and Board Characteristics with Green CEO as a Moderator - Mariska Ramadana; Yulias Hidayah; Ria Karina (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study aims to examine and analyze the impact of managerial ability and the roles of the Board of Directors (BOD) on sustainability performance, with a focus on green CEO as a moderating variable. The BOD roles include an educational background in accounting and foreign experience, with an emphasis on companies in Indonesia. This study employs secondary data from the Indonesia Stock Exchange (IDX), with a sample of 39 manufacturing companies from 2018 to 2022. Data analysis was conducted using Eviews 12. The findings reveal that managerial ability and directors with foreign experience significantly enhance sustainability performance, with the green CEO strengthening the positive effect of managerial ability on sustainability performance. However, directors with an accounting education background show no significant effect. This study acknowledges several limitations. First, while our sample includes multiple sectors to enhance generalizability, regional differences within Indonesia still pose challenges. Second, the complex interaction between managerial abilities, BOD roles, and the green CEO requires careful analysis to avoid confounding effects. This study introduces green CEO as a moderating factor in the relationship between managerial ability and sustainability performance, a novel approach that has received limited attention in prior research. Exploring how environmentally oriented leadership influences sustainability strategies adds a fresh dimension to the literature.